Tubal lymphangioma associated with ectopic pregnancy: a rare case report - P., Sakthidasan Chinnathambi; Afsar, Nabila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Cavernous lymphangioma is a rare benign lymphatic neoplasm which occurs in occur in oral cavity, limbs, and abdomen. Presentation of cavernous lymphangioma of the fallopian tube is extremely rare. Cavernous lymphangioma presenting in a case of ectopic pregnancy is discussed below.